2024
DOI: 10.1038/s41467-024-47777-5
|View full text |Cite
|
Sign up to set email alerts
|

Ambient carbon dioxide concentration correlates with SARS-CoV-2 aerostability and infection risk

Allen Haddrell,
Henry Oswin,
Mara Otero-Fernandez
et al.

Abstract: An improved understanding of the underlying physicochemical properties of respiratory aerosol that influence viral infectivity may open new avenues to mitigate the transmission of respiratory diseases such as COVID-19. Previous studies have shown that an increase in the pH of respiratory aerosols following generation due to changes in the gas-particle partitioning of pH buffering bicarbonate ions and carbon dioxide is a significant factor in reducing SARS-CoV-2 infectivity. We show here that a significant incr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Haddrell et al [65] demonstrated that the introduction of HNO 3 to the system had minimal effects on virus stability, contrary to the prediction of Luo et al [55]. Haddrell et al [65] further demonstrated that increasing the gaseous CO 2 concentration increased the stability of SARS-CoV-2 in aerosols [74]. Results align with a study on SARS-CoV-1 that observed infectivity was sensitive to both acidic conditions (pH 1-3) and alkaline conditions (pH 12-14) but stable at pH 5-9 [63].…”
Section: Ph Impact On Virus Stabilitymentioning
confidence: 98%
See 4 more Smart Citations
“…Haddrell et al [65] demonstrated that the introduction of HNO 3 to the system had minimal effects on virus stability, contrary to the prediction of Luo et al [55]. Haddrell et al [65] further demonstrated that increasing the gaseous CO 2 concentration increased the stability of SARS-CoV-2 in aerosols [74]. Results align with a study on SARS-CoV-1 that observed infectivity was sensitive to both acidic conditions (pH 1-3) and alkaline conditions (pH 12-14) but stable at pH 5-9 [63].…”
Section: Ph Impact On Virus Stabilitymentioning
confidence: 98%
“…Thus, plots of virus infectivity as a function of time may appear to have a discontinuity between the first and second phases of decay if ambient RH is below the efflorescence RH. Haddrell et al [74] described three phases of decay: a lag phase, a dynamic phase and a slow decay phase, where the dynamic phase corresponds to efflorescence or other rapidly changing conditions in a particle.…”
Section: Biphasic Decay Of Virusmentioning
confidence: 99%
See 3 more Smart Citations